2023
DOI: 10.1002/ohn.249
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tumor‐Infiltrating Lymphocytes on Disease Progression in Human Papillomavirus‐Related Oropharyngeal Carcinoma

Abstract: ObjectiveWe aim to explore the prognostic value of tumor‐infiltrating lymphocytes (TILs) in the primary tumor and metastatic lymph nodes of patients with HPV(+)OPSCC. We hypothesize that TILS density at both sites is associated with disease‐free survival in HPV(+)OPSCC.Study DesignMatched case‐control study among HPV(+)OPSCC patients who underwent intent‐to‐cure surgery. Cases developed locoregional or distant recurrence. Controls were matched based on age, sex, pathologic T, N, and overall stage, year of surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The methodology for the identification and selection of this matched case-control cohort has been previously published [13]. After obtaining institutional review board approval (IRB 20-012036), we queried a departmental REDCap oropharyngeal database to identify patients with HPV(+) OPSCC of the tonsil or base of the tongue who underwent intent-to-cure surgery +/- adjuvant therapy between 05/2007 and 12/2016.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The methodology for the identification and selection of this matched case-control cohort has been previously published [13]. After obtaining institutional review board approval (IRB 20-012036), we queried a departmental REDCap oropharyngeal database to identify patients with HPV(+) OPSCC of the tonsil or base of the tongue who underwent intent-to-cure surgery +/- adjuvant therapy between 05/2007 and 12/2016.…”
Section: Methodsmentioning
confidence: 99%
“…We compared manual annotation and DL for TILs density assessment. In our previous study, manual annotation categorized the TIL density into three groups: <10%, 10-39%, and ≥40% [13]. We applied the same classification criteria for the DL approach to calculate the ratio of TILs to tumor tiles to measure TIL density.…”
Section: Comparison Of Manual Annotation and DL Approach For Assessin...mentioning
confidence: 99%
See 1 more Smart Citation
“…The methodology for the identi cation and selection of this matched case-control cohort has been previously published [13]. After obtaining institutional review board approval (IRB 20-012036), we queried a departmental REDCap oropharyngeal database to identify patients with HPV(+) OPSCC of the tonsil or base of the tongue who underwent intent-to-cure surgery +/-adjuvant therapy between 05/2007 and 12/2016.…”
Section: Patient Cohortmentioning
confidence: 99%
“…While some studies have reported a signi cant association between TILs and survival in HPV(+) OPSCC, others suggest that TIL density may be prognostic only in lower-stage disease [12]. However, most of these TIL-based analyses rely on manual quanti cation performed by pathologists, which introduces inherent inter-observer variability even among experts [13] and is prohibitively time-consuming for clinical use.…”
Section: Introductionmentioning
confidence: 99%